2018
DOI: 10.1029/2018gl078011
|View full text |Cite
|
Sign up to set email alerts
|

Jupiter's Influence on the Building Blocks of Mars and Earth

Abstract: Radiometric dating indicates that Mars accreted in the first ~4 Myr of the solar system, coinciding with the formation and possible migration of Jupiter. While nebular gas from the protoplanetary disk was still present, Jupiter may have migrated inward and tacked at 1.5 AU in a 3:2 resonance with Saturn. This migration excited planetary building blocks in the inner solar system, resulting in extensive mixing and planetesimal removal. Here we evaluate the plausible nature of Mars's building blocks, focusing in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 51 publications
3
29
0
Order By: Relevance
“…Its bulk composition is suggested to be 45% enstatite chondrite and 55% ordinary chondrite to account for the planet's documented 17 O, 50 Ti, 54 Cr, 62 Ni, and 92 Mo isotopic values as determined from the martian meteorites (Sanloup et al 1999;Tang & Dauphas 2014). With a more rigorous analysis of uncertainties, Brasser et al (2018) recorded 29-68% entatite chondrite and 32-67% ordinary chondrite in their analysis, which is in agreement with previous studies within uncertainties. The generally much higher portion of ordinary chondrite in Mars as compared to Earth underscores the differences in bulk composition between the two planets.…”
Section: Bulk Compositional Differences Between Earth and Marssupporting
confidence: 88%
See 1 more Smart Citation
“…Its bulk composition is suggested to be 45% enstatite chondrite and 55% ordinary chondrite to account for the planet's documented 17 O, 50 Ti, 54 Cr, 62 Ni, and 92 Mo isotopic values as determined from the martian meteorites (Sanloup et al 1999;Tang & Dauphas 2014). With a more rigorous analysis of uncertainties, Brasser et al (2018) recorded 29-68% entatite chondrite and 32-67% ordinary chondrite in their analysis, which is in agreement with previous studies within uncertainties. The generally much higher portion of ordinary chondrite in Mars as compared to Earth underscores the differences in bulk composition between the two planets.…”
Section: Bulk Compositional Differences Between Earth and Marssupporting
confidence: 88%
“…Therefore, the key here is whether or not a particular break location exists at which we can reproduce the measured isotopic composition for both Earth and Mars simultaneously. Brasser et al (2018) reported a best-fit composition of 68% +0 −39 enstatite chondrite plus 32% +35 −0 ordinary chondrite for Mars, whereas Mars is suggested to be 45% enstatite chondrite and 55% ordinary chondrite according to Sanloup et al (1999) and Tang & Dauphas (2014). The break location in between 1.1 and 1.5 AU for both models can satisfy the average bulk composition of Mars in Fig.…”
Section: Chondrite Fractions To Make Earth and Marsmentioning
confidence: 64%
“…All of these models can reproduce the mass-orbital distance relation of the terrestrial planets and their orbital excitation with various degrees of success. When tied to the documented compositions of the sampled Solar System (Earth, Moon, Mars and asteroids), some are also deemed better than others at reproducing the isotopic composition of the terrestrial planets (Brasser et al, , 2018Woo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Earth accreted mostly from enstatite chondrite-like sources (Dauphas, 2017;Brasser et al, 2018;Javoy et al, 2010), which has a far lower water content (~0.01 wt%) (Hutson and Ruzicka, 2000) than ordinary chondrite (~0.1 wt%) (McNaughton et al, 1981;Robert et al, 1977Robert et al, , 1979. Based on these analyses, we conclude that the higher portion of ordinary chondrite (Woo et al, 2018;Brasser et al, 2018) together with the low fraction of water-rich carbonaceous chondrite (5 -10 wt%) (Kerridge, 1985;Robert and Epstein, 1982) delivered most of the martian water. The total estimated initial martian water budget from the coupled dynamical-cosmochemical modeling results of Brasser et al (2018) and Woo et al (2018) corresponds to ~600 ppm, which is somewhat higher than Mars' current computed bulk water content of 300 ±150 ppm (Taylor, 2013).…”
Section: A Temporary Hydrogen Atmosphere As a Byproduct Of Colossal Imentioning
confidence: 70%
“…Based on these analyses, we conclude that the higher portion of ordinary chondrite (Woo et al, 2018;Brasser et al, 2018) together with the low fraction of water-rich carbonaceous chondrite (5 -10 wt%) (Kerridge, 1985;Robert and Epstein, 1982) delivered most of the martian water. The total estimated initial martian water budget from the coupled dynamical-cosmochemical modeling results of Brasser et al (2018) and Woo et al (2018) corresponds to ~600 ppm, which is somewhat higher than Mars' current computed bulk water content of 300 ±150 ppm (Taylor, 2013). If most of the water in the martian mantle outgassed during magma ocean solidification and condensed within ~0.1…”
Section: A Temporary Hydrogen Atmosphere As a Byproduct Of Colossal Imentioning
confidence: 87%